Making Space for Social Time: Supporting Conversational Transitions Before, During, and After Video Meetings - Diaz, Carlos Gonzalez; Tang, John; Sarkar, Advait; Rintel, Sean (CHIWORK 2022, 2022)
Unlike meetings in person, it is a well known but still unsolved problem that in traditional videoconferencing people just appear and disappear [56]. The lack of Conversational Transitions (CTs) is unnatural and also limits the both ritualistic and spontaneous small talk of collegiality and productivity that happen in transitional moments. We report a design investigation of the pros and cons of a CT-Space UI that that intertwines spatial and temporal metaphors to support a range of conversational transitions before, during, and after meetings, but, crucially, might also fit into standard periodic workplace practices rather than require all-day connection. We explore the comprehensibility of visual transitions in space, how spatial audio supports transitions, blending spatial and temporal metaphors, and fluid and visible group clustering. We argue that CTs should be a standard requirement for videoconferencing services.